Knowledge, Awareness, Perceptions, and Use of Emergency Contraceptives among Survivors of Intimate Partner Violence - Kathleen J. Wilder; Jeane-Marie Guise; Nancy A. Perrin; Ginger C. Hanson; Rebecca Hernandez; Nancy Glass (Obstetrics and Gynecology International)
The study examines emergency contraception (EC) knowledge, awareness, perceptions, and prior use and identifies predictors of EC use among a sample of survivors of intimate partner violence (IPV). The majority (66.2%) of 154 survivors at risk of pregnancy reported EC awareness, only 15.3% reported prior EC use. Logistic regression identified perceived abusive intimate partner approval (OR = 2.25; 95% CI = 1.15–4.41) and lack of moral/religious objections (OR = 12.83; 95% CI = 5.48–30.03) as the strongest predictors of EC use. Health care provider interventions acknowledging barriers to EC use, such as partner approval, and education that improves awareness of and knowledge about EC, may have the impact of empowering survivors in their reproductive choices, reducing unwanted pregnancies.